Development of a didactic kit with the ESP32 microcontroller - Santos, Beatriz Correia; Azevedo, Jessamine Maria de Lima; Torné, Israel Gondres; Lima, Victor Norton; Cardoso, Fabio de Sousa; Printes, Andre Luiz (Seven Editora, 2023)
Microcontroller-based kits are used for the development of different projects and in different areas of knowledge. The main objective of this project is to develop a didactic kit that can help teachers in the classroom, and make programming practice more accessible to students, as well as obtaining more knowledge about the ESP32 microcontroller and the various peripherals (sensors and actuators). that will be present in the kit, overcoming the difficulties that exist in the execution of practices inside and outside the classroom. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-164